Prosody and particles: a study of interaction in a Malaysian academic meeting - Zuraidah Mohd Don; Tam, Shu Sim (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article examines prosody in interaction in the context of a 66 minute meeting to agree on assessment marks as part of a pilot project studying assessment procedures. The data is drawn from a larger set of data of approximately 10 hours of academic meetings. The three participants are female colleagues involved in English Language teaching. The raw data in the audio file was subjected to a three stage process of annotation, analysis and presentation. Findings show that particles can be sorted into emotive particles, artefacts of vocalisation, and those concerned with the sharing of knowledge between speaker and addressee. They can also be classified according to their relationship to speech, and whether or not they are linguistically and phonologically organised. What is also interesting is that when prosody co-occurs with particles it operates in a different way than when it illustrates syntactic or information structure or plays a role in turn taking. Prosody appears to operate as an independent component of particles, using salience to draw attention, or lack of salience to accompany activities which are not intended as interruptions.